2006
DOI: 10.1038/sj.gt.3302836
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of diabetes using a novel GLP-1/IgG1-Fc fusion construct normalizes glucose levels in db/db mice

Abstract: Glucagon-like peptide (GLP-1), a major physiological incretin, plays numerous important roles in modulating blood glucose homeostasis and has been proposed for the treatment of type 2 diabetes. The major obstacles for using native GLP-1 as a therapeutic agent are that it must be delivered by a parenteral route and has a short half-life. In an attempt to develop a strategy to prolong the physiological t 1/2 and enhance the potency of GLP-1, a fusion protein consisting of active human GLP-1 and mouse IgG 1 heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 70 publications
4
74
1
Order By: Relevance
“…This sustained increase in insulin correlated with a sustained GLP-1 expression in plasma ( Figure 2) and improved glucose tolerance. It has also been reported that GLP-1 could stabilize insulin mRNA and increase insulin transcription, consistent with recent results where increased serum insulin levels were shown in GLP-1/IgG1-Fc-treated db/db mice 47 and our pVax1-GLP-1-treated ZDF rats. However, there have been several reports showing that serum insulin levels in GLP-1-treated animals decreased because of an improvement in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This sustained increase in insulin correlated with a sustained GLP-1 expression in plasma ( Figure 2) and improved glucose tolerance. It has also been reported that GLP-1 could stabilize insulin mRNA and increase insulin transcription, consistent with recent results where increased serum insulin levels were shown in GLP-1/IgG1-Fc-treated db/db mice 47 and our pVax1-GLP-1-treated ZDF rats. However, there have been several reports showing that serum insulin levels in GLP-1-treated animals decreased because of an improvement in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…injection of a plasmid expressing a GLP-1/IgG-Fc fusion construct significantly lowered fasting blood glucose levels in db/db mice and enhanced b-cell mass in streptozocin-induced type 1 diabetes. 47 Adenoviral expression vectors, encoding GLP-1 linked to a leader sequences, have also been developed and have produced a promising re-establishment of homeostatic glucose levels in diabetic animal models such as ZDF, db/db mice and non-obese diabetic/severe combined immunodeficiency mice. 48,58 When compared with these previous studies, chitosan-mediated gene delivery of recombinant GLP-1 showed an enhanced longevity of expression and glucose normoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusion: Administration of GLP-1 via this method did have long lasting anti-diabetogenic effect on these animals. (Kumar et al, 2006) Table 4 In vitro cell systems used to study the differentiation properties of GLP-1R agonists in various cell types. Monkey Embryonic Stem Cells Ex-4 (1 nM) C-peptide, PDX-1 and NeuroD expressed in treated cells Expanded clonal population of mouse pancreatic neuroendocrineEx-4 (10 nM) Used in the culture medium along with other pancreatic hormone differentiation factors, 130 bFGF, EGF and Activin-A (Seaberg et al, 2004) …”
Section: % Partial Pancreatectomy Balb/c Mice and Glp-1r −/−mentioning
confidence: 99%
“…[53][54][55] Others have fused GLP-1 to various proteins such as IgG or albumin to improve circulating half-lives. 18,56 In each of these studies, the therapeutic effects of GLP-1 were achieved following systemic increase in GLP-1 levels. Although continuous infusion of GLP-1 in humans has not been associated with decreased receptor activation, the effects associated with chronic and continuous high levels of circulating GLP-1 are likely not yet fully appreciated.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 99%